Ethical Leadership in Educational Administration: International Perspectives and Lessons Learned - Valley, Cr Castro (Jurnal Ar Ro'is Mandalika (Armada), 2023)
Ethical leadership in educational administration is a crucial component in fostering integrity, accountability, and trust within educational institutions. This article explores international perspectives and lessons learned regarding ethical leadership in educational administration through qualitative analysis, literature review, and library research. By examining various case studies, scholarly articles, and theoretical frameworks, this study elucidates the significance of ethical leadership in promoting organizational effectiveness and student success. The analysis delves into key principles and practices of ethical leadership, including transparency, fairness, moral courage, and ethical decision-making. Moreover, it examines the challenges and opportunities faced by educational leaders in upholding ethical standards amidst complex educational landscapes and diverse cultural contexts. Through this comprehensive exploration, the article aims to contribute to a deeper understanding of ethical leadership in educational administration and provide insights for practitioners, policymakers, and researchers worldwide.